Variabilitas Genetik Ornithoptera croesus lydius Kupu-Kupu Endemik Pulau Halmahera Berbasis Data Molekuler PCR-RAPD - Mas'ud, Abdu; Abdullah, Abubakar; Roini, Chumidach (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
Ornithoptera croesus lydius is one of endemic butterlfy in Halmahera island North Maluku. It is macrolepidotera tipe, with interesting colour body at male and female butterfly. At Ornithoptera croesus lydius male and female butterfly have variation morphology size and colour body. The genetic variability on the O.c lydius butterflies is level intraspecies variability. The objective of the research is to know the genetic variability on the O.c lydius based on PCR-RAPD marker. The most value of genetic distance is 0,783 on O.c lydius male and female from hotspot at 780 masl. The percentage of polimorphic is 71,95%. Base on similarity value and polymorphic percentage show genetic variability on intraspecies level of the Ornithoptera croesus lydius.